The language Defamiliarization in the stories of Ale Ahmad (based on Modir Madreseh and Panj Dastan) - سمیّه صادقیان (مطالعات زبانی و بلاغی)
Formalists considered that the function of literature was to "defamilarize" the ordinary and the everyday perception of surroundings. A literary text is derived from “defamiliarization” techniques at different levels of form, meaning and even literary genres. Constructivists extended this topic and proposed the literary role as one of the linguistic roles, which is formed by “defamiliarization” in language. Therefore, they expressed various kinds of “defamiliarization” and “foregrounding” in language. By studying the language used by Al-e Ahmad in his two books entitled “Modir-e Madreseh” (The School Principal) and “Panj Dastan” (Five Stories), we find examples for what are referred to as “foregrounding techniques”, we also come across with examples that “defamilarize” the language; although they are not developed by linguists. In addition to employing some common and pervasive syntactic deviation cases, Al-e Ahmad uses the colloquial language in a new beautiful form as the story language. By summarizing in many ways, he becomes author of “telegraphic prose” and extends the semantic area of words.